The role of the state in the system of currency -financial export promotion - E. A. Barinov (Путеводитель предпринимателя)
In the article on the example of some foreign countries focuses on the practice of state support of national exporters and purchasing them from foreign importers of goods and services. Attention is paid to the issue of withdrawal of Russian companies on foreign markets. Analyzing the system of support to Russian exports and the problem of perfection.